Quantitative phosphoproteome on the silkworm (Bombyx mori) cells infected with baculovirus - Jauharotus Shobahah; Shengjie Xue; Dongbing Hu; Cui Zhao; Ming Wei; Yanping Quan; Wei Yu (Virology Journal, 2017)
Abstract Background Bombyx mori has become an important model organism for many fundamental studies. Bombyx mori nucleopolyhedrovirus (BmNPV) is a significant pathogen to Bombyx mori, yet also an efficient vector for recombinant protein production. A previous study indicated that acetylation plays many vital roles in several cellular processes of Bombyx mori while global phosphorylation pattern upon BmNPV infection remains elusive. Method Employing tandem mass tag (TMT) labeling and phosphorylation affinity enrichment followed by high-resolution LC-MS/MS analysis and intensive bioinformatics analysis, the quantitative phosphoproteome in Bombyx mori cells infected by BmNPV at 24 hpi with an MOI of 10 was extensively examined. Results Totally, 6480 phosphorylation sites in 2112 protein groups were identified, among which 4764 sites in 1717 proteins were quantified. Among the quantified proteins, 81 up-regulated and 25 down-regulated sites were identified with significant criteria (the quantitative ratio above 1.3 was considered as up-regulation and below 0.77 was considered as down-regulation) and with significant p-value (p < 0.05). Some proteins of BmNPV were also hyperphosphorylated during infection, such as P6.9, 39 K, LEF-6, Ac58-like protein, Ac82-like protein and BRO-D. Conclusion The phosphorylated proteins were primary involved in several specific functions, out of which, we focused on the binding activity, protein synthesis, viral replication and apoptosis through kinase activity.